Sodium and Potassium Fluxes in Isolated Barnacle Muscle Fibers - Brinley, F. J. (The Rockefeller University Press, 1968)
Sodium and potassium influxes and outfluxes have been studied in single isolated muscle fibers from the giant barnacle both by microinjection and by external loading. The sodium influxes and outfluxes were 49 and 39 pmoles /cm(2)-sec (temperature = 15–16°C) respectively. The potassium influxes and outfluxes were 28 and 60 pmoles/cm(2)-sec (temperature = 13–16°C) respectively. Replacement of external sodium by lithium reduced sodium outflux by 67% but had no effect on potassium outflux. Removal of external potassum reduced the sodium outflux by 51% but had no effect on potassium outflux. External strophanthidin (10–30 µM) reduced sodium outflux by 80–90% and increased potassium outflux by 40% in normal fibers. The time constant for sodium exchange increased linearly with internal sodium concentration, as did the fraction of sodium outflux insensitive to a maximally inhibitory concentration of external strophanthidin in the range of 10 tO 80 mM internal sodium. The strophanthidin-sensitive component of sodium outflux could be related to the internal sodium concentration by the following empirical formula: See PDF for Equation